Methane Isotopes from the WAIS Divide Ice Core - Sowers, Todd A. (IEDA: US Antarctic Program Data Center, 2009)
Abstract: This data set includes methane (CH4) isotope data from the West Antarctic Ice Sheet (WAIS) Divide ice core, WDC05A, in Antarctica. The data include depth, gas age, and the isotopic composition of methane (∂13C and ∂D of CH4). The ice core was collected during the 2005-2006 Antarctic field season. The CH4 isotope data was generated in 2008 using wet extraction methodology. Samples span the last 1,000 years, at a resolution of about 15 years. Data for samples above 69 meters were from firn air, and data below 69 meters from ice. The dating of the ice was based on continuous chemical analyses above 69 meters and Electrical Conductivity/Dielectric Property (ECM/DEP) measurements from ice. Dating uncertainty is estimated to be better than five years. Data are available via FTP in Microsoft Excel (.xls) tab delimited format